Which are important targets in development of S. aureus mastitis vaccine?. (June 2015) - Scali, F.; Camussone, C.; Calvinho, L.F.; Cipolla, M.; Zecconi, A.
Highlights: Concerns on antibiotics usages emphasize interest in S. aureus mastitis vaccines. S. aureus has a large amount of virulence factors and selecting them is hard. Vaccines do not provide consistent protection against S. aureus IMI. Host immune response to S. aureus vaccination needs additional investigations. Abstract: Staphylococcus aureus represents one of the leading causes of mastitis in dairy cows worldwide. S. aureus IMI have variable outcomes due to virulence of the strain involved, immune defenses of the host, and by antibiotic resistance. The difficulty in eradication and the increasing concerns on antibiotics usages underscore the interest in developing new tools to control S. aureus mastitis. Vaccination represents one of the most studied of these tools but, so far, no vaccine seems to provide reliable protection. This review summarizes current knowledge on the major vaccine targets, including surface proteins, capsular polysaccharides, biofilm, and toxins. Finally, the present status of vaccination against S. aureus and the future of vaccine design were discussed, including how differences among in vivo models may influence vaccines development.